Manajemen Konflik Lembaga Pendidikan Dasar Islam - Samsudin, Samsudin; Setyowati, Nanik (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
Conflicts in educational institutions can have a significant positive or negative effect on educational institutions, educators, and education personnel who work there. So conflicts in Islamic basic education institutions must be managed properly to minimize their impact. The purpose of this study is to find the concept of conflict management in Islamic Educational Institutions that is by the values ​​of Islamic teachings. The approach in this study is a descriptive-interpretative qualitative approach. The type of research used is library research. While the data obtained are descriptive narrative data about conflict management in Islamic Elementary Education Institutions, among others; friendship as an effort to prevent conflict, doing bahts al masaail as a form of blocking the occurrence of conflict, tabayyun in the context of conflict regulation, mediator as conflict institutionalization, and finally ishlah as a conflict resolution process.